Sistem Informasi Penerimaan Siswa Baru Pada SMK Teknikom Berbasis Web Dengan PHP Dan MySQL Menggunakan Metode Waterfall - Achmad Sahril (Prosiding Sains dan Teknologi, 2022)
SMK Teknikom Cikarang is a private vocational school which is located in Sukarukun Village, Kec. Sukatani, Bekasi Regency. So far, the registration process for new students still has to fill in via Google Form so that the data is not yet integrated, and some prospective students still have to go to school and fill out the registration form. Information regarding registration is also still not conveyed effectively because on average the prospective students who apply to this school are prospective students who are no longer accepted in other schools. Not to mention the lack of information about the registration requirements that must be met by prospective students where many completeness requirements have not been met which causes prospective students to have to submit registration requirements back and forth. Reporting on registrant data is also still manual which must be recapitulated by TU officers using Excel, so that if TU officers are asked to report both the number of registrants and entry for registration, it still takes a long time to present the report. The above causes a lack of information conveyed regarding the deadline for registration, what conditions must be met to be able to enter the SMK, as well as delays in presenting information, which is an obstacle for the Principal and Foundation to make decisions in future school management. This study uses the waterfall method to design a web-based PPDB Online information system using PHP and MySQL. With the development of this system, it can assist in the process of managing the registration system for new prospective students at SMK Teknikom without having to use Google Forms again so that it is integrated with payment systems, re-registration and others and prospective students do not have to come directly to register. This system can help checklist the requirements of new prospective students that have not been met, making it easier to check for lack of requirements, making the registration process easier, from the admin side it also makes the process of checking completeness and payment transactions and re-registration more effective and efficient. In addition, problems related to the process of reporting new student registration data have become easier. Keywords: Registration, New Students, Registration Requirements, Waterfall, Php Mysql